A COMPARATIVE ANALYSIS OF CLOUD, FOG & EDGE COMPUTING (International Journal of Engineering Sciences & Management Research, 2021)
This paper presents a complete comparative analysis of Cloud, Edge, and Fog Computing, describing their architectures, capabilities, and applications. Tremendously growing need for low latency, efficient data management, and real-time processing hasgiven rise to the emergence of these computing paradigms. This paper explores prospective integration strategies and synergies to optimize computing resources in a varied range of applications.Edge computing is a distributed technology architecture in which client data is processed at the edge of the enterprise network, as close to the producing source as possible.Fog computing is taking the benefits of cloud computing to the edge of the network. It specifies non centralized computing resource located between the devices that produce data and the cloud. Tasks like computing, storing, and networking between devices and data centers of cloud computing are being provided by Fog computing. Decentralization and flexibility are the primary differences between Fog computing and Cloud computing. Reduced latency, comfiture network bandwidth, reduced operating costs, improved security, and enhanced reliability are primary advantages of Fog computing. Various applications of Fog computing aresmart electric grids, smart transportation networks, autonomous connected cars, smart citiesand real-time analysis, etc., This paper shows a comparative study of Cloud, Fog, and Edge Computing.